UNETHICAL BEHAVIOR OF STUDENTS ON EXAMS (Zdravstveni glasnik, 2024)
Introduction: The unethical behavior of students on exams represents a serious challenge for the education system. This disturbing trend requires immediate attention and the implementation of appropriate measures to raise awareness about the importance of academic integrity and promote ethical awareness among students.Objective: Examine the unethical behavior of students on exams.Subjects and methods: The study involved students from the Medical School in Šibenik. Out of the total number of participants, 155 students took part, with 75 (48,4%) specializing in general nursing, and 80 (51,6%) in pharmaceutical studies. The participants completed a questionnaire based on the Šimić Šašić and Klarin model (2009).Results: The results showed a high percentage of cheating during knowledge assessments. A total of 81,9% of respondents admitted to cheating at least once. In the domain of attitudes towards the acceptability of cheating, 52,9% of respondents agreed that cheating is entirely natural and inherent to human nature. Regarding different grades, fourth-grade students significantly held a stronger attitude toward the acceptability of cheating compared to students from other grades. Regarding reasons for cheating, the most common internal reason, stated by 50,4 % of respondents, was insufficient time for studying, while 49.6% cheated to help a friend, and 49% cheated to achieve good grades. External reasons for cheating, such as weak supervision, were mentioned by 52,9% of respondents, unfairness by 52,2%, and difficulty of the exam by 49% of respondents. Female respondents exhibited more pronounced internal and external reasons for cheating compared to male respondents. Conclusion: The research confirmed that academic dishonesty is a routine occurrence among students. The students themselves do not view cheating as ethically wrong and rationalize it in numerous ways.